Effect of garlic (Allium sativum) and nilavembu (Andrographis paniculata) on growth performance and cost effectiveness of broiler chicken - ARIFY, TORYALI; VALAVAN, S EZHIL; VARUN, A; SUNDARESAN, A; MANIMARAN, K (The Indian Journal of Animal Sciences, 2019)
The biological experiment was conducted to study the effect of feeding garlic (Allium sativum) and nilavembu (Andrographis paniculata) in broiler chicken (Vencobb 400) for a period of 6 weeks on various parameters, viz. biweekly body weight, gain in body weight, feed conversion ratio, livability and the cost effectiveness of feeding garlic and nilavembu. A total of 300 day-old, unsexed, broiler chicken were utilized for this study. The treatment groups were fed with diets containing garlic and nilavembu at different levels, such as control (T1), 5 g garlic + 1 g nilavembu (T2), 10 g garlic + 1 g nilavembu (T3), 5 g garlic + 2 g nilavembu (T4) and 10 g garlic + 2 g nilavembu (T5), respectively. Biological experiment revealed that there was highly significant (P